Small conductance calcium-activated potassium channels and nitric oxide/cGMP pathway mediate cardioprotective effects of Croton urucurana Baill. In hypertensive rats. (15th July 2022) - Lopes, Katiana Simões; Marques, Aline Aparecida Macedo; Moreno, Karyne Garcia Tafarelo; Lorençone, Bethânia Rosa; Leite, Patrícia Regina Terço; da Silva, Gabriela Pereira; dos Santos, Ariany Carvalho; Souza, Roosevelt Isaías Carvalho; Gasparotto, Francielly Mourão; Cassemiro, Nadla Soares; Lourenço, Emerson Luiz Botelho; Klider, Lislaine Maria; et al.
Abstract: Ethnopharmacological relevance: Croton urucurana Baill. (Euphorbiaceae), popularly known as 'sangue de dragão' is a Brazilian species widely used in traditional medicine for cardiovascular ailments. Aim: To investigate the cardiovascular effects of the C. urucurana extract in spontaneously hypertensive rats (SHRs). Materials and methods: Leaves from C. urucurana were collected and morphoanatomically characterized. The ethanol-soluble fraction (ESCU) was obtained and analyzed by LC-DAD-MS. Using female Wistar rats we investigated the acute toxicity of ESCU. Then, SHRs (six months old) received vehicle, hydrochlorothiazide (25 mg/kg), or ESCU (30, 100, 300 mg/kg) for 28 days. At the beginning and at the end of treatments, urine samples were obtained to assess renal function. At the end of the trial period, the blood pressure, mesenteric vascular beds (MVBs) reactivity, and electrocardiographic profile were evaluated. Serum angiotensin-converting enzyme activity, as well as urea, creatinine, sodium, potassium, nitrite, malondialdehyde, nitrotyrosine, and aldosterone levels were determined. Relative organ weights and histopathological analysis were performed. Finally, the cardiac function on a Langendorff system, as well as the molecular mechanisms involved in the vasodilator effects of ESCU in MVBs were also investigated. Results: The compounds annotated from ESCU by LC-DAD-MS included mainly phenylpropanoid derivatives, alkaloids, O-glycosylated megastigmanes, glycosylated flavonoids, flavan-3-ols, and others, such as quercetin O-deoxyhexosyl-hexoside, magnoflorine, reticuline, and taspine. None of the animals showed any signs of toxicity. Male SHRs treated only with the vehicle showed important cardiovascular changes, including a reduction in renal function, increase in serum oxidative stress, and hemodynamic, electrocardiographic, and morphological changes typical of hypertensive disease. Moreover, parameters of cardiac function, including left ventricular developed pressure, peak rate of contraction, peak rate of relaxation, and the rate pressure product were significantly altered, showing a significant impairment of ventricular function. All ESCU-doses presented a significant cardioprotective effect in SHRs rats. The 28-day treatment normalized the hemodynamic, electrocardiographic, morphological, and renal impairments, as well as reversed the changes in ventricular function induced by hypertension. In MVBs with an intact endothelium, ESCU (0.1, 0.3, and 1 mg) dose-dependently induced vasodilation. Endothelium removal or the inhibition of nitric oxide synthase prevented the vasodilatory effect of ESCU. Perfusion with a physiological saline solution that contained KCl, tetraethylammonium, or apamin also abolished the vasodilatory effect of ESCU. Conclusion: Prolonged ESCU-treatment showed significant cardioprotective effects in SHRs. Moreover, the data showed the role of nitric oxide and calcium-activated small conductance potassium channels in the cardiovascular effects of ESCU. Graphical abstract: Image 1 Highlights: Croton urucurana extract (ESCU) is used in Brazilian traditional medicine for the treatment of cardiovascular diseases. We evaluated the cardioprotective effects induced by ESCU on male spontaneously hypertensive rats (SHR). Prolonged ESCU-treatment normalized all renal and cardiovascular alterations in SHR. C. urucurana showed cardioprotective effects by nitric oxide pathway and Ca 2+ activated small conductance K + channels.